Effect of Beta-Alanine supplementation on 800-m running performance - Ducker, K. J.; Dawson, B.; Wallman, K. E. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Beta-alanine supplementation has been shown to improve exercise performance in short-term, high-intensity efforts. Purpose: The aim of this study was to assess if beta-alanine supplementation could improve 800 m track running performance in male recreational club runners (n = 18). Methods: Participants completed duplicate trials (2 presupplementation, 2 postsupplementation) of an 800 m race, separated by 28 days of either beta-alanine (n = 9; 80 mg·kg-1BM·day-1) or placebo (n = 9) supplementation. Results: Using ANCOVA (presupplementa- tion times as covariate), postsupplementation race times were significantly faster following beta-alanine (p = .02), with post- versus presupplementation race times being faster after beta-alanine (-3.64 ± 2.70 s, -2.46 ± 1.80%) but not placebo (-0.59 ± 2.54 s, -0.37 ± 1.62%). These improvements were supported by a moderate effect size (d = 0.70) and a very likely (99%) benefit in the beta-alanine group after supplementation. Split times (ANCOVA) at 400 m were significantly faster (p = .02) postsupplementation in the beta-alanine group, compared with placebo. This was supported by large effect sizes (d = 1.05-1.19) and a very likely (99%) benefit at the 400 and 800 m splits when comparing pre- to postsupplementation with beta-alanine. In addition, the first and second halves of the race were faster post- compared with presupplementation following beta-alanine (1st half -1.22 ± 1.81 s, likely 78% chance of benefit; 2nd half -2.38 ± 2.31 s, d = 0.83, very likely 98% chance of benefit). No significant differences between groups or pre- and postsupplementation were observed for postrace blood lactate and pH. Conclusion: Overall, 28 days of beta-alanine supplementation (80 mg·kg-1BM·day-1) improved 800 m track performance in recreational club runners.